Diagnosis of Tuberculosis by an Enzyme-Linked Immunospot Assay for Interferon-γ - Jann-Yuan Wang; Chien-Hong Chou; Li-Na Lee; Hsiao-Leng Hsu; I-Shiow Jan; Po-Ren Hsueh; Chuan-Liang Kao; Kwen-Tay Luh (Emerging Infectious Diseases, 2007)
We evaluated an enzyme-linked immunospot assay for interferon-γ (T SPOT-TB) for rapid diagnosis of active tuberculosis (TB) in a disease-endemic area. From January to June 2005, patients whose clinical symptoms and radiographic findings were compatible with TB were recruited, and a blood sample was obtained for T SPOT-TB assay within 7 days of microbiologic studies. Sixty-five patients were studied, including 39 (60%) with active TB. Thirty-five (53.8%) patients had underlying medical conditions. Thirty-seven patients had positive cultures for Mycobacterium tuberculosis, and 11 patients had positive cultures for nontuberculous mycobacteria. The sensitivity, specificity, positive predictive value, and negative predictive value of the T SPOT-TB assay were 87.2%, 88.5%, 91.9%, and 82.1%, respectively. The accuracy of this test in diagnosing active TB is >80%, even in an area with a high incidence of nontuberculous mycobacteria disease.